Fatigue in primary Sjögren's syndrome: A proteomic pilot study of cerebrospinal fluid. (May 2019) - Larssen, Eivind; Brede, Cato; Hjelle, Anne; Tjensvoll, Anne Bolette; Norheim, Katrine Brække; Bårdsen, Kjetil; Jonsdottir, Kristin; Ruoff, Peter; Omdal, Roald; Nilsen, Mari Mæland
Objectives: Fatigue is a frequent and often disabling phenomenon that occurs in patients with chronic inflammatory and immunological diseases, and the underlying biological mechanisms are largely unknown. Because fatigue is generated in the brain, we aimed to investigate cerebrospinal fluid and search for molecules that participate in the pathophysiology of fatigue processes. Methods: A label-free shotgun proteomics approach was applied to analyze the cerebrospinal fluid proteome of 20 patients with primary Sjögren's syndrome. Fatigue was measured with the fatigue visual analog scale. Results: A total of 828 proteins were identified and the 15 top discriminatory proteins between patients with high and low fatigue were selected. Among these were apolipoprotein A4, hemopexin, pigment epithelium-derived factor, secretogranin-1, secretogranin-3, selenium-binding protein 1, and complement factor B. Conclusion: Most of the discriminatory proteins have important roles in regulation of innate immunity, cellular stress defense, and/or functions in the central nervous system. These proteins and their interacting protein networks may therefore have central roles in the generation and regulation of fatigue, and the findings contribute with evidence to the concept of fatigue as a biological phenomenon signaled through specific molecular pathways.